2009
DOI: 10.1007/s12325-009-0015-8
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-dose manidipine/delapril versus losartan/hydrochlorothiazide in hypertensive patients with type 2 diabetes and microalbuminuria

Abstract: A fixed-dose manidipine/delapril combination represents a useful addition to the treatment options available to control hypertension complicated by diabetes and microalbuminuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Extremely wide credible intervals were noted for the treatments of ARB plus calcium channel blocker, ARB plus diuretic, and ACE inhibitor plus ARB, indicating great uncertainty in the estimation of treatment effect owing to small patient numbers and rare death events among those treatment arms. Sensitivity analyses showed robust results (see supplementary table E) since the rank ordering and statistical significance remained the same after omitting studies comparing with either ARB plus calcium channel blocker,27 ARB plus diuretic,28 or ACE inhibitor plus ARB 29. The combination therapy of ACE inhibitor plus calcium channel blocker showed the highest probability of being at the best ranking position, whereas the sensitivity analysis showed that omitting such a treatment arm did not impact on the ranking order and statistical significance of the remaining treatments (see supplementary table E).…”
Section: Resultsmentioning
confidence: 95%
“…Extremely wide credible intervals were noted for the treatments of ARB plus calcium channel blocker, ARB plus diuretic, and ACE inhibitor plus ARB, indicating great uncertainty in the estimation of treatment effect owing to small patient numbers and rare death events among those treatment arms. Sensitivity analyses showed robust results (see supplementary table E) since the rank ordering and statistical significance remained the same after omitting studies comparing with either ARB plus calcium channel blocker,27 ARB plus diuretic,28 or ACE inhibitor plus ARB 29. The combination therapy of ACE inhibitor plus calcium channel blocker showed the highest probability of being at the best ranking position, whereas the sensitivity analysis showed that omitting such a treatment arm did not impact on the ranking order and statistical significance of the remaining treatments (see supplementary table E).…”
Section: Resultsmentioning
confidence: 95%
“…Among them, 8 RCTs recruited Asian subjects only, [ 13 15 , 18 , 20 , 21 , 23 , 24 ] while the other 6 RCTs were conducted in either mixed-race or unmentioned-race populations. Six RCTs compared the 2 combined treatments in 1001 patients with diabetes mellitus, [ 13 , 14 , 16 , 17 , 22 , 25 ] and 3 RCTs compared treatments in 1079 CKD patients. [ 19 , 23 , 24 ] Regarding the sample size, ACCOMPLISH (11,506 patients) and COLM (5141 patients) were the 2 largest RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…To assess renoprotective effects, 2 studies used 24-hour urinary albumin, [ 16 , 17 ] 3 studies used urinary ACR, [ 15 , 19 , 25 ] and 3 studies used UAE. [ 13 , 22 , 23 ] After integrating the outcomes of 24-hour urinary albumin, urinary ACR, and UAE, the meta-analysis showed that ACEI/ARB plus diuretic resulted in a 7.48% larger decline in the pooled urinary outcome, although the decline was not statistically significant (MD = 7.48%; 95% CI: −6.13% to 21.08%; P = 0.28; I 2 = 92%; Fig. 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…In other study performed in obese hypertensive patients, the delapril/manidipine combination but not the olmesartan/hydrochlorothiazide combination significantly decreased insulin resistance and plasma fibrinogen levels, despite similar BP lowering efficacy [ 94 ]. In another study performed in hypertensive patients with type 2 diabetes and microalbuminuria, whereas BP was reduced to a similar extent by both treatments after one year of follow-up, there was a trend for a reduction of blood glucose concentration from baseline with manidipine/delapril (mean change −0.2 mmol/L, p =0.064), but not with the losartan/hydrochlorothiazide combination [ 95 ].…”
Section: Manidipine: Beneficial Effects Beyond Blood Pressure Controlmentioning
confidence: 99%